Pengaruh Displin Kerja Dan Beban Kerja Terhadap Produktivitas Kerja Karyawan Pada PT Bumi Arta Mukti - Herlina Febriyanti; Rycha Kuwara Sari; Ferawaty Puspitorini (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to determine or test (1) the influence of work discipline on work productivity at PT Bumi Arta Mukti (2) the influence of workload on work productivity at PT Bumi Arta Mukti (3) the influence of work discipline and workload on work productivity at PT Bumi Arta Mukti. The type of research used in this research is quantitative research. The sampling technique in this research used saturated sampling, namely the entire population was sampled, a total of 77 employees at PT Bumi Arta Mukti. The data analysis method uses multiple linear regression, validity and reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, and hypothesis tests. The data was processed using IBM SPSS Statistics 23. The results of this research show that (1) work discipline has a positive effect on employee work productivity at PT Bumi Arta Mukti (2) workload has a positive effect on employee work productivity at PT Bumi Arta Mukti and (3) discipline work and workload influence simultaneously or together on employee work productivity at PT Bumi Arta Mukti.